Autoimmunity and autoimmune disease: A Colombian construction beyond deconstructions (2006)
The first Colombian Autoimmune Symposium held in Medellin, Colombia, February 23–25, 2005, covered the entire spectrum of the diverse aspects of autoimmunity and autoimmune disorders. The symposium originated as part of a seminar on Autoimmunity in the Master’s and Doctorate program, and approximately 250 participants, including MDs, medical students, and basic research staff attended it. Moreover, during the Symposium the book bAutoimmunity and Autoimmune DiseaseQ was launched [1]. The symposium was divided into six sessions and each one adopted a particular focus.